A new locality of Saperda (Saperda) similis (Coleoptera: Cerambycidae) in Bulgaria - Georgi Georgiev; Margarita Georgieva; Borislav Guéorgiev; Pencho Dermendzhiev; Maria Dobreva; Nikolay Zlatanov (Silva Balcanica)
A new locality of the rare species Saperda (Saperda) similis Laicharting (Coleoptera: Cerambycidae) was reported in Bulgaria. The species was reared from stems and branches of goat willow (Salix caprea), collected on 23.10.2024 in the land of Kosovo village at 1468 m a.s.l., Western Rhodopes. In laboratory conditions, three specimens emerged during the period 20 February - 4 March 2025. An old published record of S. similis (syn. Saperda phoca Frölich) was identified as Phytoecia (Danilevskia) uncinata (Redtenbacher).